Effect of Void Area on Hollow Cement Masonry Mechanical Performance - Sathiparan, N.; Anusari, M.K.N.; Samindika, N.N. (Springer, 2014)
Originally, brick/block was formed by placing moist clay/cement mortar in a mold by hand. As modern industrial methods were implemented in the cement block manufacturing process, themajority of production was changed from a molded process to an extrusion process. Extrusionmore easily accommodates the inclusion of hollow (void area) in a block unit, which in turn can make the manufacture and use of block more cost-effective and material efficient. Although void area in block varies from place to place, hollow masonry unit standards are defined by ASTM C90- 11b, and specifications are related to theminimum face shells and a web requirement. This paper examines the effect of the void area on aspects of the performance of hollow cement block masonry. The performance of five comparison sets of hollow cement masonry was evaluated for different range of void area.Water absorption, compressive strength of cement block, compressive, shear, and flexural tensile strength of masonry prism were measured on each type of hollow block and used as indicators of potential performance in a masonry wall.
Keywords: Masonry; Hollow cement block